THE ROLE OF PROBIOTICS IN ORAL HEALTH - HINDIA B; DR.V.JAYANTH KUMAR, MDS (International Journal of Pharma and Bio Sciences, 2014)
In the recent years, there is an increasing tendency among health care professionals to combat the various diseases using biological means without the use of chemical agents. It is in this regard, the role of probiotics gains significance. Probiotics are a group of bacteria, which change the ecosystem in localized areas of the body, thereby keeping the pathogenic bacteria under control. This review article highlights the applications of probiotics in dentistry in the prevention of dental caries, periodontal diseases, cancer.